Isolated retroperitoneal leiomyoma with adhesion to the iliac vessel in a middle-aged female - Thapa, Subash; Shrestha, Sebak; Shrestha, Agya; Shrestha, Bipin; Thapa, Sushmita (Journal of Chitwan Medical College, 2025)
Leiomyoma is a common benign mesenchymal tumour, but its occurrence in the retroperitoneum is rare and is referred to as retroperitoneal leiomyoma. The clinical presentation is often non-specific, leading to a diagnostic challenge for surgeons. Although preoperative diagnosis remains difficult even with radiological imaging, radiologists play a crucial role in assisting the surgical team by facilitating a multidisciplinary approach for optimal outcomes. We report the case of a 40-year-old female who presented with low back pain and abdominal discomfort for five months. Radiological imaging revealed a retroperitoneal mass possibly adherent to the left iliac vessel. The patient underwent meticulous retroperitoneal dissection, and histopathological examination confirmed the diagnosis of retroperitoneal leiomyoma.